2015
DOI: 10.1117/12.2193827
|View full text |Cite
|
Sign up to set email alerts
|

Medium altitude airborne Geiger-mode mapping LIDAR system

Abstract: Over the past 15 years the Massachusetts Institute of Technology, Lincoln Laboratory (MIT/LL), Defense Advanced Research Projects Agency (DARPA) and private industry have been developing airborne LiDAR systems based on arrays of Geiger-mode Avalanche Photodiode (GmAPD) detectors capable of detecting a single photon. The extreme sensitivity of GmAPD detectors allows operation of LiDAR sensors at unprecedented altitudes and area collection rates in excess of 1,000 km 2 /hr. Up until now the primary emphasis of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 12 publications
0
16
0
Order By: Relevance
“…The 1064 nm wavelength is sometimes touted as having several natural advantages including: (1) a factor of 3 lower solar background; (2) generally higher reflectances from natural surfaces such as soil/dry vegetation (25% vs. 15%) and green vegetation (65% vs. 10%); (3) slightly better atmospheric transmission; and (4) no frequency conversion losses in laser power which are typically on the order of 40% to 50% [2,15]. The 532 nm wavelength benefits from: (1) the availability of relatively mature and inexpensive, high efficiency array detectors and narrowband spectral filters; (2) detector dark count contributions to background noise are typically much lower in the visible spectrum; and (3) good transmission in water columns which allows solid land topography and bathymetry to be performed by a single instrument at a single wavelength as in Figure 13.…”
Section: Key Differences Between Spl and Gm Lidarsmentioning
confidence: 99%
See 3 more Smart Citations
“…The 1064 nm wavelength is sometimes touted as having several natural advantages including: (1) a factor of 3 lower solar background; (2) generally higher reflectances from natural surfaces such as soil/dry vegetation (25% vs. 15%) and green vegetation (65% vs. 10%); (3) slightly better atmospheric transmission; and (4) no frequency conversion losses in laser power which are typically on the order of 40% to 50% [2,15]. The 532 nm wavelength benefits from: (1) the availability of relatively mature and inexpensive, high efficiency array detectors and narrowband spectral filters; (2) detector dark count contributions to background noise are typically much lower in the visible spectrum; and (3) good transmission in water columns which allows solid land topography and bathymetry to be performed by a single instrument at a single wavelength as in Figure 13.…”
Section: Key Differences Between Spl and Gm Lidarsmentioning
confidence: 99%
“…Later generations included the medium altitude Airborne Lidar Research Testbed (ALIRT), and the High Altitude Lidar Operations Experiment (HALOE) [13,14]. More recently, DARPA transferred GMAPD technology from MIT/LL to commercial entities, and Harris Corporation has introduced the first commercial GM system, The IntelliEarth™ Geospatial Solutions Geigermode Lidar Sensor [15].…”
Section: Single Photon Lidar (Spl) Vs Geiger Mode (Gm) Lidarmentioning
confidence: 99%
See 2 more Smart Citations
“…Along with advancements in data acquisition (e.g., [13]), 3D reconstruction [3], and applications [2], 3D city models have become common geospatial data assets for cities. A comprehensive study by [14] already identified over one thousand 3D city models worldwide.…”
Section: Introductionmentioning
confidence: 99%